Relative Energy Deficiency in Sport (REDs) and knee injuries: current concepts for female athletes - Wang, M.; Chee, J.; Tanaka, M. J.; Lee, J. H. D. (Journal of ISAKOS, 2024)
In athletes, a mismatch between caloric intake and energy expended in exercise can eventually lead to Relative Energy Deficiency in Sport (REDs), where the athlete suffers from physiological derangements and decreased sport performance. The prevalence of REDs is higher in females than males. Females are already at a higher risk of knee injuries, which has been attributed to a multitude of factors such as hormonal influences, differences in musculoskeletal anatomy and neuromuscular control compared to males. The literature demonstrates an even higher risk of knee injuries in female athletes with symptoms of REDs. We propose the various factors that influence this risk. A reduction in anabolic hormones can affect muscle development and tendon repair. A relationship between poor neuromuscular control and knee injury has been established, and this can be further worsened in patients with menstrual dysfunction. Chronic deficiency in nutrients such as collagen and vitamin D can result in poorer recovery from microtrauma in tendons and ligaments. All these factors may contribute to increasing the risk of knee injuries, which may include anterior cruciate ligament tears, patella tendinopathy and patellofemoral pain syndrome. This review aims to educate sports clinicians to have a high index of suspicion when treating knee injuries in females; to screen and then manage for REDs if present, for holistic patient care.